Influence of ARHGEF3 and RHOA Knockdown on ACTA2 and Other Genes in Osteoblasts and Osteoclasts - Mullin, B.; Mamotte, Cyril; Prince, R.; Wilson, S. (Public Library of Science, 2014)
Osteoporosis is a common bone disease that has a strong genetic component. Genome-wide linkage studies have identified the chromosomal region 3p14-p22 as a quantitative trait locus for bone mineral density (BMD). We have previously identified associations between variation in two related genes located in 3p14-p22, ARHGEF3 and RHOA, and BMD in women. In this study we performed knockdown of these genes using small interfering RNA (siRNA) in human osteoblast-like and osteoclast-like cells in culture, with subsequent microarray analysis to identify genes differentially regulated from a list of 264 candidate genes. Validation of selected findings was then carried out in additional human cell lines/cultures using quantitative real-time PCR (qRT-PCR). The qRT-PCR results showed significant down-regulation of the ACTA2 gene, encoding the cytoskeletal protein alpha 2 actin, in response to RHOA knockdown in both osteoblast-like (P<0.001) and osteoclast-like cells (P = 0.002). RHOA knockdown also caused up-regulation of the PTH1R gene, encoding the parathyroid hormone 1 receptor, in Saos-2 osteoblast-like cells (P<0.001). Other findings included down-regulation of the TNFRSF11B gene, encoding osteoprotegerin, in response to ARHGEF3 knockdown in the Saos-2 and hFOB 1.19 osteoblast-like cells (P = 0.003– 0.02), and down-regulation of ARHGDIA, encoding the Rho GDP dissociation inhibitor alpha, in response to RHOA knockdown in osteoclast-like cells (P<0.001). These studies identify ARHGEF3 and RHOA as potential regulators of a number of genes in bone cells, including TNFRSF11B, ARHGDIA, PTH1R and ACTA2, with influences on the latter evident in both osteoblast-like and osteoclast-like cells. This adds further evidence to previous studies suggesting a role for the ARHGEF3 and RHOA genes in bone metabolism.